Super-lubricity antifouling coating with high-adhesion biofilm structure and preparation method of super-lubricity antifouling coating
By forming a biofilm scaffold structure by mesophilic adhesion, combined with glutaraldehyde fixation and silanization treatment, the preparation problems and production complexity of ultra-slip antifouling coatings in the prior art on a variety of substrates are solved, and an efficient and universal ultra-slip antifouling coating is achieved, with excellent corrosion resistance and mechanical properties.
Patent Information
- Application Number
- CN202510397347.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-01
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2045-04-01
AI Technical Summary
The prior art is difficult to prepare efficient ultra-slip anti-fouling coatings on a variety of substrates, and the production method is complex and time-consuming, and the paradox of internal surface roughness makes interface slip, high light transmittance and mechanical flexibility difficult to achieve simultaneously.
The biofilm scaffold structure is formed by culture of the mesotherophilic adhesion bacteria. Adhesion and hydrophobicity are enhanced through glutaraldehyde fixation and silanization treatment, and combined with the lubricant to form a superslip anti-fouling coating with a high-adhesion biofilm structure.
It has achieved the preparation of universal, scalable, difficult to adsorption, antibacterial and antifouling super-slip coatings on a variety of substrates, with excellent corrosion resistance and mechanical properties, and overcomes the inconsistency between repellency and mechanical properties of traditional coatings.
Smart Images

Figure CN119897257A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of marine antifouling and anticorrosion, and particularly relates to an ultra-slip antifouling coating with a high-adhesion biofilm structure and a preparation method thereof. Background Art
[0002] Marine corrosion and biofouling are the most serious threats to the safety of marine engineering equipment and offshore structures. High-salinity environments accelerate the corrosion of marine engineering equipment and offshore structures, and marine biofouling has a harmful impact on marine aquaculture, shipping and oil production. These fouling organisms colonize on underwater surfaces, resulting in impaired equipment performance, increased fuel consumption or structural damage. Biofouling is characterized by the harmful accumulation of biomolecules and microorganisms, posing a serious threat to public health, marine infrastructure and offshore. This microbially mediated process can also accelerate the deterioration of metals by establishing a corrosive microenvironment and promoting microbial corrosion, with harmful consequences for economic development and environmental damage. In the past few decades, liquid-repellent surfaces have emerged as a promising strategy to mitigate biofouling. Superhydrophobic surfaces inspired by lotus leaves, with their air-trapping surface texture and low surface chemical energy, effectively repel water droplets and inhibit fouling bioadhesion; however, this external metastable air cushion collapses easily under harsh marine conditions (e.g., high temperature, high pressure, and high humidity). The resulting Cassie state to Wenzel state transition significantly reduces the mobility of droplets and induces surface pinning, providing an ecological site for biofouling colonization. Recalcitrant surface colonization can exacerbate metal corrosion by up to four orders of magnitude. Inspired by pitcher plants, a slippery liquid-infused porous surface (SLIPS) has recently been proposed as an alternative to traditional superhydrophobic surfaces, which is of great significance for metal protection.
[0003] Although technicians in this field are committed to carefully designing various super-slippery coatings controlled by surface morphology and chemical characteristics, the current methods for designing highly structured roughness, first, involve harsh and time-consuming preparation procedures, and the increased cost, low stability and unsustainable production of the materials used have greatly hindered large-scale applications; second, there are few schemes that can fabricate complex nanoscale textures compatible with various substrates (such as metals, ceramics, polymers and fabrics), especially on the internal surfaces of confined cavity spaces; finally, due to the paradox of intrinsic surface roughness, it seems difficult to simultaneously achieve interfacial slip, high transmittance and mechanical flexibility in a single coating, which hinders the realization of universally applicable repellent surfaces.
[0004] Microorganisms that are ubiquitous in nature have evolved to anchor themselves in one location, forming flexible biofilm interfaces on the Earth's surface to protect themselves from the harsh environment, rather than as planktonic cells. Compared with traditional organic and inorganic platforms, biofilms containing more than 90% (w / w) extracellular polymers (EPS) provide a unique three-dimensional network with high surface area, tunable surface chemical energy, and strong interfacial adhesion, which is theoretically an ideal structure that meets the rough structure of ultra-slippery coatings. However, most microorganisms exhibit highly dynamic growth behavior and weak and unstable biofilm formation ability, which limits their attachment to material interfaces.
[0005] Regarding the research on the preparation of super-slip coatings with multiple functions of anti-corrosion and anti-fouling, there are currently patents with publication number CN117926362A for a metal substrate surface composite coating and its preparation method and application, and patent publication number CN116288576A for an electrodeposition method of a super-hydrophobic and super-slip coating on a weathering steel surface. The above-mentioned super-slip coatings are produced by a relatively complex micro-arc oxidation and electrodeposition method to create roughness on the metal surface; such coatings have two disadvantages: first, they can only be applied on metal surfaces, are difficult to be successfully prepared on a variety of substrates, and are not universal; second, the production method is complicated, time-consuming, and has high requirements on the conditions required for the production process. Summary of the invention
[0006] In view of the problems existing in the prior art, the research objective of the present invention is to provide an ultra-slip antifouling coating with a high-adhesion biofilm structure and a preparation method thereof. SLIPS, which is based on an anti-corrosion biofilm structure, uses a biofilm as a scaffold structure, and forms a stable rough structure attached to the surface of a substrate material through the growth of the biofilm. The EPS in the bacterial biofilm is bonded to the substrate material through ionic bonds and chemical bonds, and has better adhesion. After the anti-corrosion biofilm structure is treated with silanization, the surface of the biofilm is in an oleophilic and hydrophobic state, which is conducive to compounding with a lubricant, so as to obtain an ultra-slip coating with multiple functions such as universal, expandable, difficult to adsorb, antibacterial and antifouling, and has a universal ultra-slip and antifouling effect on corrosive media, proteins, bacteria and algae.
[0007] In order to achieve the above object, the technical solution adopted by the present invention is as follows: The present invention provides a method for preparing an ultra-slip antifouling coating with a high-adhesion biofilm structure, comprising the following steps: Step 1: Cultivate the mesophilic adhesin bacteria, adjust the bacterial concentration, obtain a bacterial culture solution, place the material sample in the bacterial culture solution for cultivation, and cover the surface of the material sample with a biofilm scaffold structure; Step 2: The material sample covering the biofilm scaffold structure is appropriately rinsed aseptically to remove floating bacteria, and fixed with glutaraldehyde to obtain a biofilm material sample base; Step 3: Activate the biofilm material sample substrate to eliminate surface adsorbed water and generate more surface reactive groups; Step 4: performing dry or wet silanization treatment on the activated biofilm material sample substrate to deposit hydrophobic silane on the biofilm structure surface of the material sample to obtain a hydrophobic-biofilm structure coating of the material sample; Step 5: Inject the lubricant into the hydrophobic-biofilm structure coating of the material sample, absorb it through capillary force to form an outer coating, adjust the inclination angle of the material sample so that the lubricant is evenly and fully covered on the surface of the hydrophobic-biofilm structure coating of the material sample, and obtain an ultra-slip anti-fouling coating with a high adhesion biofilm structure.
[0008] Furthermore, in step 1, the culture of the mesophilic adhesin Bacillus is performed by inoculating the separated single colony of the mesophilic adhesin Bacillus into 2216E liquid culture medium using a plate streak method, the culture temperature is 20° C.-40° C., and the culture is performed until it is in the logarithmic growth phase.
[0009] Furthermore, in step 1, the bacterial concentration was adjusted to 10 5 CFU / mL-10 8 CFU / mL.
[0010] Furthermore, the material samples described in step 1 include metal, glass and polymer. The metal samples are surface polished, cleaned and dried before being placed in the bacterial culture solution, and the glass and polymer are cleaned and dried before being placed in the bacterial culture solution; the material samples are cultured in the bacterial culture solution for 3 to 5 days.
[0011] Furthermore, in step 2, sterile phosphate buffered saline (sterile PBS solution) is used for sterile flushing; The concentration of glutaraldehyde in glutaraldehyde fixation is 2%-6% (v / v), and the fixation time is 2h-8h.
[0012] Furthermore, in step 3, activation is performed by oxygen plasma treatment for 1 min to 5 min.
[0013] Furthermore, in step 4, the dry silanization treatment is to place the biofilm material sample in a vacuum dryer and treat it with n-octyltriethoxysilane chemical vapor deposition at room temperature to achieve in-situ hydrolysis and condensation reaction of silane on the biofilm; The wet silanization treatment is to immerse the biofilm material sample in an ethanol / water solution containing n-octyltriethoxysilane.
[0014] Furthermore, in step 4, in the dry silanization treatment, n-octyltriethoxysilane is used for chemical vapor deposition treatment for 12h-36h; The volume ratio of n-octyltriethoxysilane to ethanol / water solution in wet silanization treatment is 1:1, and the immersion time is 3h-6h.
[0015] Furthermore, in step 5, the lubricant is silicone oil.
[0016] The present invention provides an ultra-slip antifouling coating with a high-adhesion biofilm structure, which is prepared using a method for preparing an ultra-slip antifouling coating with a high-adhesion biofilm structure. The ultra-slip antifouling coating is a slippery liquid-injected porous surface (SLIPS) of an anti-corrosion biofilm structure, uses the biofilm as a support structure, has a nano-scale texture, deposits hydrophobic silane on the surface of the biofilm structure, and is compounded with a lubricant.
[0017] Compared with the prior art, the ultra-slip antifouling coating with a high-adhesion biofilm structure and the preparation method thereof of the present invention have the following beneficial effects: 1. The present invention innovatively uses self-growing organisms to formulate interface morphology, giving it certain characteristics to facilitate the manufacture of expandable integrated coatings. Based on the porous surface characteristics of natural anticorrosive biofilms and injected lubricants, the smooth surface is combined with unique biopolymers; by depositing hydrophobic silanes and then injecting lubricants in situ liquid curing, a uniform, conformal, highly adherent biofilm structured ultra-slip antifouling coating is prepared, which can achieve dual mitigation of biofouling and microbial corrosion under complex marine environmental conditions, and provide broad-spectrum corrosion resistance to corrosive media, proteins, bacteria and algae.
[0018] 2. The present invention not only successfully realizes the natural anticorrosive biofilm as a rough structure source for multifunctional coatings, but also provides a highly adaptive biofilm-derived interface for potential applications across energy, environment and biomedical fields.
[0019] 3. The present invention uses an aerobic marine strain, Bacillus thuringiensis, which is well-known for producing highly adhesive biofilms under mild conditions. Bacillus thuringiensis is a Gram-negative bacterium widely distributed in the marine environment. It has the potential function of a sustainable source and antiseptic biopolymer, and has shown excellent biofilm-forming ability in more than 30 tested species, and can form a stable, interconnected, dense biofilm on the surface of the material.
[0020] 4. The present invention fixes the biofilm by glutaraldehyde, thereby enhancing its adhesion to the surface of the material sample.
[0021] 5. The present invention performs silanization treatment on the biofilm structure and uses n-octyltriethoxysilane to perform in-situ covalent silane grafting, thereby producing an oleophilic and hydrophobic chemical layer with a strong affinity for the lubricant, which is beneficial to further lubricant compounding. After the lubricant silicone oil is injected for wetting, a stable lubricant covering layer is formed, which has good diffusion parameters, thereby producing a biofilm-derived smooth repellent coating in a highly synergistic manner, that is, an ultra-slip antifouling coating of a high-adhesion biofilm structure, which overcomes the inconsistency between the repellency and mechanical properties of traditional coatings.
[0022] 6. The biofilm structure of the present invention has high cohesion, is derived from sustainable raw materials, and can be used as an inanimate biomaterial scaffold to form ultra-slip coating nanoscale textures without further processing.
[0023] 7. The preparation method of the ultra-slip antifouling coating with a high-adhesion biofilm structure of the present invention is simple, easy to implement, environmentally friendly, and scalable. It customizes an innovative and sustainably produced biomaterial to provide a strong, adhesive, and universal coating that can accurately adjust the thickness of the biofilm structure skeleton at the nanoscale, thereby forming a stable and ultra-thin lubricant layer.
[0024] 8. The ultra-slip antifouling coating with a high-adhesion biofilm structure of the present invention is an effective strategy for marine antifouling. It has a universal ultra-slip antifouling effect on corrosive media, proteins, bacteria and algae. It is stable and universal when used to prevent marine biological fouling and corrosion. It has a protein resistance of 72.3%, a bacteria resistance of 96.28%, and an algae resistance of 85.72%. It has excellent corrosion resistance, provides a new way for the development of efficient antifouling means in marine engineering, and is also an effective application of engineering biofilms in practice. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a comparison chart of the biofilm formation ability of Mesophilic Adhesive Bacillus in Example 1 of the present invention and Shewanella Oneida in Comparative Example 1 on 304 stainless steel; Figure 2 Atomic force microscope (AFM) images showing the microstructure and roughness of the biofilm support structure, hydrophobic-biofilm structure coating and high-adhesion biofilm structure super-slip anti-fouling coating of the 304 stainless steel sample in Example 1 of the present invention, wherein: (a) is the biofilm support structure, (b) is the hydrophobic-biofilm structure coating, and (c) is the high-adhesion biofilm structure super-slip anti-fouling coating; Figure 3 The Fourier transform infrared spectra (FTIR) of the biofilm scaffold structure and the hydrophobic-biofilm structure coating of the 304 stainless steel sample in Example 1 of the present invention are shown; Figure 4The transmission electron microscope (TEM) images of the hydrophobic-biofilm structure coating of Example 1 of the present invention are shown in FIG. 1 , wherein: (a) is a TEM dark field image, and (b) is a TEM bright field image; Figure 5 This is an energy dispersive spectroscopy (EDS) diagram of the hydrophobic-biofilm structure coating of Example 1 of the present invention, wherein: (a) is Si element, (b) is O element, (c) is C element, and (d) is N element; Figure 6 is the transmittance of the blank glass and the hydrophobic-biofilm structure coating and the highly adhesive biofilm structure super-slip antifouling coating on the glass substrate in Example 6 of the present invention measured by an ultraviolet spectrophotometer in the range of 400 nm-800 nm; Figure 7 The water contact angle and water sliding angle of the ultra-slip antifouling coating with a high-adhesion biofilm structure obtained by adopting the preparation method of Example 1 of the present invention and only changing the culture time of the sample in the bacterial culture solution to form the biofilm structure; Figure 8 The water contact angle and water sliding angle of the ultra-slip antifouling coating with high adhesion biofilm structure prepared on different substrates in Examples 5 to 11 of the present invention; Fig. 9 The ultra-slip antifouling coating surface of the high-adhesion biofilm structure of the 304 stainless steel substrate in Example 5 of the present invention and the time-lapse snapshot of a 10 μL water droplet sliding on the surface of the 304 stainless steel substrate in the blank group, wherein: (a) is a t=0.00s photo of the blank group, (b) is a t=3.00s photo of the blank group, (c) is a t=0.00s photo of Example 5, and (d) is a t=5.00s photo of Example 5; Fig.10 The ultra-slip antifouling coating surface of the high-adhesion biofilm structure of the Teflon substrate in Example 7 of the present invention and the time-lapse snapshot of a 10 μL water droplet sliding on the Teflon substrate surface of the blank group, wherein: (a) is a t=0.00s photo of the blank group, (b) is a t=2.00s photo of the blank group, (c) is a t=0.00s photo of Example 5, and (d) is a t=2.00s photo of Example 5; Fig.11 The ultra-slip antifouling coating with high adhesion biofilm structure on the inner wall of the PVC tube in Example 12 of the present invention and the time-lapse snapshots of a 10 μL water droplet sliding on the inner wall of the PVC tube of the blank group, wherein: (a) is a photo of the blank group at t=0.00s, (b) is a photo of the blank group at t=3.00s, (c) is a photo of the blank group at t=6.00s, (d) is a photo of Example 12 at t=0.00s, (e) is a photo of Example 12 at t=2.00s, and (f) is a photo of Example 12 at t=4.00s; Fig.12The water sliding angle of the ultra-slip antifouling coating of the high-adhesion biofilm structure of the PET sheet in Example 8 of the present invention after being bent into U, V and S shapes for 1000 bending cycles, wherein: (a) is a schematic diagram of U-shaped bending, (b) is a schematic diagram of V-shaped bending, (c) is a schematic diagram of S-shaped bending, and (d) is a diagram showing the change of water sliding angle during the bending cycle; Fig.13 Electrochemical impedance spectra of the 304 stainless steel substrate with ultra-slip antifouling coating of high-adhesion biofilm structure in Example 1 of the present invention, the 304 stainless steel substrate with ultra-slip coating of biofilm structure in Comparative Example 1, and the 304 stainless steel substrate in the blank group after being immersed in a Pseudomonas aeruginosa solution for 4 days; Fig.14 This is a comparison chart of the colony count changes of Escherichia coli, Staphylococcus aureus and Bacillus vietnamense measured by the dilution coating plate method for the hydrophobic-biofilm structure coating, the ultra-slip antifouling coating 304 stainless steel substrate with a high adhesion biofilm structure and the blank group 304 stainless steel substrate in Example 1 of the present invention; Fig.15 This is a comparison chart of the algae resistance test results of the hydrophobic-biofilm structure coating, the ultra-slip antifouling coating 304 stainless steel substrate with a high adhesion biofilm structure, and the blank group 304 stainless steel substrate to Chlorella and Isochrysis in Example 1 of the present invention. DETAILED DESCRIPTION
[0026] The technical scheme and technical effects of the present invention are described in detail below in conjunction with specific embodiments and drawings. Experimental methods without specifying specific conditions are usually based on conventional conditions, such as the conditions described in textbooks and experimental guides, or the conditions recommended by manufacturers, which are well known or easily known to ordinary technicians in the field. The following embodiments are only preferred embodiments of the present invention and do not limit the present invention. For those skilled in the art, the present invention can have various changes and variations. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
[0027] Example 1 The present invention provides a method for preparing an ultra-slip antifouling coating with a high-adhesion biofilm structure, comprising the following steps: Step 1: A single colony of the mesophilic adhesinophilic Bacillus isolated by the plate streak method was inoculated into 2216E liquid culture medium and cultured at 30°C for 12 h until the logarithmic growth phase. The bacterial concentration was adjusted to 10 6 CFU / mL obtained bacterial culture solution; The 1 cm × 1 cm 304 stainless steel samples were surface-polished with 240, 400, 600, 800, and 1000 grit sandpaper, then ultrasonically cleaned in a mixed solution of ethanol and acetone for 30 minutes and then dried; The 304 stainless steel sample was placed in a bacterial culture medium for culture. After 4 days of culture, a mesophilic adhesinic bacillus biofilm scaffold structure was routinely formed on the surface of the 304 stainless steel sample.
[0028] Step 2: The 304 stainless steel sample covered with the biofilm support structure was gently rinsed with a sterile PBS solution to remove the planktonic mesophilic adhesin bacteria, and fixed with 4% (v / v) glutaraldehyde for 2 h to obtain the biofilm 304 stainless steel sample substrate.
[0029] Step 3: The biofilm 304 stainless steel sample substrate was activated with oxygen plasma for 1 min to eliminate the surface adsorbed water and generate more surface reactive groups.
[0030] Step 4: The activated biofilm 304 stainless steel sample is subjected to dry (chemical vapor deposition) silanization treatment. The biofilm 304 stainless steel sample is placed in a vacuum desiccator and treated with 100 μL of n-octyltriethoxysilane chemical vapor deposition at room temperature for 24 hours. The silane undergoes in situ hydrolysis and condensation reactions on the biofilm, thereby introducing a surface layer of repellent silane on the biofilm, that is, forming a silane hydrophobic layer on the surface of the biofilm structure of the 304 stainless steel sample, thereby obtaining a hydrophobic-biofilm structure coating of the 304 stainless steel sample.
[0031] Step 5: Take 20 μL of silicone oil and inject it into the hydrophobic-biofilm structure coating of the 304 stainless steel sample to form an outer coating through capillary absorption. Adjust the inclination angle of the 304 stainless steel sample to make the lubricant evenly and fully cover the surface of the hydrophobic-biofilm structure coating of the 304 stainless steel sample to obtain an ultra-slip anti-fouling coating with a high adhesion biofilm structure.
[0032] Example 2 The present invention provides a method for preparing an ultra-slip antifouling coating with a high-adhesion biofilm structure, comprising the following steps: Step 1: A single colony of the mesophilic adhesinophilic Bacillus isolated by the plate streak method was inoculated into 2216E liquid culture medium and cultured at 30°C for 12 h until the logarithmic growth phase. The bacterial concentration was adjusted to 10 6 CFU / mL obtained bacterial culture solution; The 1 cm × 1 cm 304 stainless steel samples were surface-polished with 240, 400, 600, 800, and 1000 grit sandpaper, then ultrasonically cleaned in a mixed solution of ethanol and acetone for 30 minutes and then dried; The 304 stainless steel sample was placed in a bacterial culture medium for culture. After 3 days of culture, a mesophilic adhesinic bacillus biofilm scaffold structure was routinely formed on the surface of the 304 stainless steel sample.
[0033] Step 2: The 304 stainless steel sample covered with the biofilm support structure was gently rinsed with a sterile PBS solution to remove the planktonic mesophilic adhesin bacteria, and fixed with 4% (v / v) glutaraldehyde for 2 h to obtain the biofilm 304 stainless steel sample substrate.
[0034] Step 3: The biofilm 304 stainless steel sample substrate was activated with oxygen plasma for 1 min to eliminate the surface adsorbed water and generate more surface reactive groups.
[0035] Step 4: The activated biofilm 304 stainless steel sample is subjected to wet silanization treatment. The biofilm 304 stainless steel sample is immersed in an ethanol / water solution containing n-octyltriethoxysilane for 3 hours. The volume ratio of n-octyltriethoxysilane to ethanol / water solution is 1:1, thereby introducing a surface layer of repellent silane on the biofilm, that is, forming a silane hydrophobic layer on the surface of the biofilm structure of the 304 stainless steel sample, and obtaining a hydrophobic-biofilm structure coating of the 304 stainless steel sample.
[0036] Step 5: Take 20 μL of silicone oil and inject it into the hydrophobic-biofilm structure coating of the 304 stainless steel sample to form an outer coating through capillary absorption. Adjust the inclination angle of the 304 stainless steel so that the lubricant is evenly and fully covered on the surface of the hydrophobic-biofilm structure coating of the 304 stainless steel to obtain an ultra-slip anti-fouling coating with a high adhesion biofilm structure.
[0037] Example 3 The present invention provides a method for preparing an ultra-slip antifouling coating with a high-adhesion biofilm structure, comprising the following steps: Step 1: A single colony of the mesophilic adhesinophilic Bacillus isolated by the plate streak method was inoculated into 2216E liquid culture medium and cultured at 30°C for 12 h until the logarithmic growth phase. The bacterial concentration was adjusted to 10 6 CFU / mL, bacterial culture fluid was obtained; The 1 cm × 1 cm (supplemental sample size) 304 stainless steel samples were surface-polished with 240, 400, 600, 800, and 1000 grit sandpaper, then ultrasonically cleaned in a mixed solution of ethanol and acetone for 30 min, and then blown dry; The 304 stainless steel sample was placed in a bacterial culture solution for culture. After 5 days of culture, a mesophilic adhesinic bacillus biofilm scaffold structure was routinely formed on the surface of the 304 stainless steel sample.
[0038] Step 2: The 304 stainless steel sample covered with the biofilm support structure was gently rinsed with a sterile PBS solution to remove the planktonic mesophilic adhesin bacteria, and fixed with 4% (v / v) glutaraldehyde for 2 h to obtain the biofilm 304 stainless steel sample substrate.
[0039] Step 3: The biofilm 304 stainless steel sample substrate was activated with oxygen plasma for 2 min to eliminate the surface adsorbed water and generate more surface reactive groups.
[0040] Step 4: The activated biofilm 304 stainless steel sample is subjected to wet silanization treatment. The biofilm 304 stainless steel sample is immersed in an ethanol / water solution containing n-octyltriethoxysilane for 4 hours. The volume ratio of n-octyltriethoxysilane to ethanol / water solution is 1:1, thereby introducing a surface layer of repellent silane on the biofilm, that is, forming a silane hydrophobic layer on the surface of the biofilm structure of the ceramic sample, and obtaining a hydrophobic-biofilm structure coating of the 304 stainless steel sample.
[0041] Step 5: Take 20 μL of silicone oil and inject it into the hydrophobic-biofilm structure coating of the 304 stainless steel sample to form an outer coating through capillary absorption. Adjust the inclination angle of the 304 stainless steel sample to make the lubricant evenly and fully cover the surface of the hydrophobic-biofilm coating of the ceramic sample to obtain an ultra-slip anti-fouling coating with a high adhesion biofilm structure.
[0042] Example 4 The present invention provides a method for preparing an ultra-slip antifouling coating with a high-adhesion biofilm structure, comprising the following steps: Step 1: A single colony of the mesophilic adhesinophilic Bacillus isolated by the plate streak method was inoculated into 2216E liquid culture medium and cultured at 30°C for 12 h until the logarithmic growth phase. The bacterial concentration was adjusted to 10 6 CFU / mL obtained bacterial culture solution; The 1 cm × 1 cm 304 stainless steel samples were surface-polished with 240, 400, 600, 800, and 1000 grit sandpaper, then ultrasonically cleaned in a mixed solution of ethanol and acetone for 30 minutes and then dried; The 304 stainless steel sample was placed in a bacterial culture medium for culture. After 4 days of culture, a mesophilic adhesinic bacillus biofilm scaffold structure was routinely formed on the surface of the 304 stainless steel sample.
[0043] Step 2: The 304 stainless steel sample covered with the biofilm support structure was gently rinsed with a sterile PBS solution to remove the planktonic mesophilic adhesin bacteria, and fixed with 4% (v / v) glutaraldehyde for 2 h to obtain the biofilm 304 stainless steel sample substrate.
[0044] Step 3: The biofilm 304 stainless steel sample substrate was activated with oxygen plasma for 3 min to eliminate the surface adsorbed water and generate more surface reactive groups.
[0045] Step 4: The activated biofilm 304 stainless steel sample is subjected to wet silanization treatment. The biofilm 304 stainless steel sample is immersed in an ethanol / water solution containing n-octyltriethoxysilane for 6 hours. The volume ratio of n-octyltriethoxysilane to ethanol / water solution is 1:1, thereby introducing a surface layer of repellent silane on the biofilm, that is, forming a silane hydrophobic layer on the surface of the biofilm structure of the ceramic sample, and obtaining a hydrophobic-biofilm structure coating of the 304 stainless steel sample.
[0046] Step 5: Take 20 μL of silicone oil and inject it into the hydrophobic-biofilm structure coating of the 304 stainless steel sample to form an outer coating through capillary absorption. Adjust the inclination angle of the 304 stainless steel sample so that the lubricant is evenly and fully covered on the surface of the hydrophobic-biofilm coating of the 304 stainless steel sample to obtain an ultra-slip anti-fouling coating with a high adhesion biofilm structure.
[0047] Example 5 The present invention provides a method for preparing an ultra-slip antifouling coating with a high-adhesion biofilm structure, comprising the following steps: Step 1: A single colony of the mesophilic adhesinophilic Bacillus isolated by the plate streak method was inoculated into 2216 E liquid medium and cultured at 30°C for 12 h until the logarithmic growth phase. The bacterial concentration was adjusted to 10 8 CFU / mL obtained bacterial culture solution; The 7.62 cm × 2.54 cm 304 stainless steel samples were surface-polished with 240, 400, 600, 800, and 1000 grit sandpaper, then ultrasonically cleaned in a mixed solution of ethanol and acetone for 30 minutes and then dried; The 304 stainless steel sample was placed in a bacterial culture medium for culture. After 4 days of culture, a mesophilic adhesinic bacillus biofilm scaffold structure was routinely formed on the surface of the 304 stainless steel sample.
[0048] Step 2: The 304 stainless steel sample covered with the biofilm support structure was gently rinsed with a sterile PBS solution to remove the planktonic mesophilic adhesin bacteria, and fixed with 2% (v / v) glutaraldehyde for 8 hours to obtain the biofilm 304 stainless steel sample substrate.
[0049] Step 3: The biofilm 304 stainless steel sample substrate was activated with oxygen plasma for 5 min to eliminate the surface adsorbed water and generate more surface reactive groups.
[0050] Step 4: The activated biofilm 304 stainless steel sample is subjected to dry (chemical vapor deposition) silanization treatment. The biofilm 304 stainless steel sample is placed in a vacuum desiccator and treated with 100 μL of n-octyltriethoxysilane chemical vapor deposition at room temperature for 36 hours. The silane undergoes in situ hydrolysis and condensation reactions on the biofilm, thereby introducing a surface layer of repellent silane on the biofilm, that is, forming a silane hydrophobic layer on the surface of the biofilm structure of the 304 stainless steel sample, thereby obtaining a hydrophobic-biofilm structure coating of the 304 stainless steel sample.
[0051] Step 5: Take 400 μL of silicone oil and inject it into the hydrophobic-biofilm structure coating of the 304 stainless steel sample to form an outer coating through capillary absorption. Adjust the inclination angle of the 304 stainless steel sample so that the lubricant is evenly and fully covered on the surface of the hydrophobic-biofilm coating of the 304 stainless steel sample to obtain an ultra-slip anti-fouling coating with a high adhesion biofilm structure.
[0052] Example 6 The present invention provides a method for preparing an ultra-slip antifouling coating with a high-adhesion biofilm structure, comprising the following steps: Step 1: A single colony of the mesophilic adhesinophilic Bacillus isolated by the plate streak method was inoculated into 2216E liquid culture medium and cultured at 30°C for 12 h until the logarithmic growth phase. The bacterial concentration was adjusted to 10 5 CFU / mL obtained bacterial culture solution; A 7.62 cm × 2.54 cm glass sample was ultrasonically cleaned in a mixed solution of ethanol and acetone for 30 minutes and then blown dry; The glass sample was placed in a bacterial culture solution for cultivation. After 4 days of cultivation, a mesophilic adhesinic bacillus biofilm scaffold structure was routinely formed on the surface of the glass sample.
[0053] Step 2: The glass sample covered with the biofilm support structure was gently rinsed with a sterile PBS solution to remove the planktonic mesophilic adhesin bacteria, and fixed with 3% (v / v) glutaraldehyde for 4 hours to obtain the biofilm glass sample substrate.
[0054] Step 3: The biofilm glass sample substrate was activated with oxygen plasma for 5 min to eliminate the water adsorbed on the surface and generate more surface reactive groups.
[0055] Step 4: Perform dry (chemical vapor deposition) silanization treatment on the activated biofilm glass sample. Place the biofilm glass sample in a vacuum desiccator and treat it with 100 μL of n-octyltriethoxysilane chemical vapor deposition for 12 hours at room temperature. The silane undergoes in situ hydrolysis and condensation reactions on the biofilm, thereby introducing a surface layer of repellent silane on the biofilm, that is, forming a silane hydrophobic layer on the surface of the biofilm structure of the glass sample, thereby obtaining a hydrophobic-biofilm structure coating of the glass sample.
[0056] Step 5: Take 400 μL of silicone oil and inject it into the hydrophobic-biofilm structure coating of the glass sample to form an outer coating through capillary absorption. Adjust the inclination angle of the glass sample to make the lubricant evenly and fully cover the surface of the hydrophobic-biofilm coating of the glass sample to obtain an ultra-slip anti-fouling coating with a high adhesion biofilm structure.
[0057] Example 7 The present invention provides a method for preparing an ultra-slip antifouling coating with a high-adhesion biofilm structure, comprising the following steps: Step 1: A single colony of the mesophilic adhesinophilic Bacillus isolated by the plate streak method was inoculated into 2216E liquid culture medium and cultured at 30°C for 12 h until the logarithmic growth phase. The bacterial concentration was adjusted to 10 8 CFU / mL obtained bacterial culture solution; A 7.62 cm × 2.54 cm piece of Teflon was ultrasonically cleaned in a mixed solution of ethanol and acetone for 30 minutes and then dried; The Teflon samples were placed in bacterial culture medium for cultivation. After 4 days of cultivation, a mesophilic adhesinic bacillus biofilm scaffold structure was routinely formed on the surface of the Teflon samples.
[0058] Step 2: The Teflon sample covered with the biofilm scaffold structure was gently rinsed with a sterile PBS solution to remove the planktonic mesophilic adhesiomycetes, and fixed with 2% (v / v) glutaraldehyde for 8 hours to obtain the biofilm Teflon sample substrate.
[0059] Step 3: The biofilm Teflon sample substrate was activated with oxygen plasma for 5 min to eliminate the water adsorbed on the surface and generate more surface reactive groups.
[0060] Step 4: Perform dry (chemical vapor deposition) silanization treatment on the activated biofilm Teflon sample. Place the biofilm Teflon sample in a vacuum desiccator and treat it with 100 μL of n-octyltriethoxysilane chemical vapor deposition for 36 hours at room temperature. The silane undergoes in situ hydrolysis and condensation reactions on the biofilm, thereby introducing a surface layer of repellent silane on the biofilm, that is, forming a silane hydrophobic layer on the surface of the biofilm structure of the Teflon sample, thereby obtaining a hydrophobic-biofilm structure coating of the Teflon sample.
[0061] Step 5: Take 400 μL of silicone oil and inject it into the hydrophobic-biofilm structure coating of the Teflon sample to form an outer coating through capillary absorption. Adjust the inclination angle of the Teflon sample to make the lubricant evenly and fully cover the surface of the hydrophobic-biofilm coating of the Teflon sample to obtain an ultra-slip anti-fouling coating with a high adhesion biofilm structure.
[0062] Example 8 The present invention provides a method for preparing an ultra-slip antifouling coating with a high-adhesion biofilm structure, comprising the following steps: Step 1: A single colony of the mesophilic adhesinophilic Bacillus isolated by the plate streak method was inoculated into 2216E liquid culture medium and cultured at 30°C for 12 h until the logarithmic growth phase. The bacterial concentration was adjusted to 10 8 CFU / mL obtained bacterial culture solution; A 7.62 cm × 2.54 cm polyethylene terephthalate (PET) sample was ultrasonically cleaned in a mixed solution of ethanol and acetone for 30 min and then dried; The PET samples were placed in bacterial culture medium for culture. After 4 days of culture, a mesophilic adhesinic bacillus biofilm scaffold structure was routinely formed on the surface of the PET samples.
[0063] Step 2: The PET sample covered with the biofilm scaffold structure was gently rinsed with a sterile PBS solution to remove the planktonic mesophilic adhesin bacteria, and fixed with 2% (v / v) glutaraldehyde for 8 hours to obtain a biofilm PET sample substrate.
[0064] Step 3: The biofilm PET sample substrate was activated with oxygen plasma for 5 min to eliminate the water adsorbed on the surface and generate more surface reactive groups.
[0065] Step 4: The activated biofilm PET sample is subjected to dry (chemical vapor deposition) silanization treatment. The biofilm PET sample is placed in a vacuum desiccator and treated with 100 μL of n-octyltriethoxysilane chemical vapor deposition for 36 hours at room temperature. The silane undergoes in situ hydrolysis and condensation reactions on the biofilm, thereby introducing a surface layer of repellent silane on the biofilm, that is, forming a silane hydrophobic layer on the surface of the biofilm structure of the PET sample, thereby obtaining a hydrophobic-biofilm structure coating of the PET sample.
[0066] Step 5: Take 400 μL of silicone oil and inject it into the hydrophobic-biofilm structure coating of the PET sample to form an outer coating through capillary absorption. Adjust the inclination angle of the PET sample to make the lubricant evenly and fully cover the surface of the hydrophobic-biofilm coating of the Teflon sample to obtain an ultra-slip anti-fouling coating with a high adhesion biofilm structure.
[0067] Example 9 The only difference from Example 5 is that the sample substrate is Ti, and an ultra-slip antifouling coating with a high-adhesion biofilm structure is prepared on the Ti sample.
[0068] Example 10 The only difference from Example 5 is that the sample substrate is Al, and an ultra-slip antifouling coating with a high-adhesion biofilm structure is prepared on the Al sample.
[0069] Embodiment 11 The only difference from Example 5 is that the sample substrate is 2205 stainless steel, and an ultra-slip antifouling coating with a high-adhesion biofilm structure is prepared on the 2205 stainless steel sample.
[0070] Example 12 The only difference from Example 8 is that the sample substrate is a polyvinyl chloride (PVC) tube with an inner diameter of 3 mm, the PVC tube is immersed in a bacterial culture solution, and an ultra-slip antifouling coating with a high adhesion biofilm structure is prepared on the inner wall of the narrow-pore PVC tube.
[0071] Comparative Example 1 The mesophilic adhesinobacterium in Example 1 was replaced with Shewanella Oneida, and the formation of the biofilm scaffold structure of Shewanella Oneida was observed.
[0072] Step 1: A single colony of Shewanella Oneida was isolated by plate streak method and inoculated into 2216E liquid medium. The culture was cultured at 30°C for 12 h until the logarithmic growth phase. The bacterial concentration was adjusted to 10 6 CFU / mL, bacterial culture fluid was obtained; The 1 cm × 1 cm 304 stainless steel samples were surface-polished with 240, 400, 600, 800, and 1000 grit sandpaper, then ultrasonically cleaned in a mixed solution of ethanol and acetone for 30 minutes and then dried; The 304 stainless steel sample was placed in a bacterial culture solution for culture. After 4 days of culture, a membrane scaffold structure of Shewanella mesophila was formed on the surface of the 304 stainless steel sample.
[0073] Step 2: The 304 stainless steel sample covered with the biofilm support structure was gently rinsed with a sterile PBS solution to remove the floating Shewanella Oneida, and fixed with 4% (v / v) glutaraldehyde for 2 hours to obtain the biofilm 304 stainless steel sample substrate.
[0074] Step 3: The biofilm 304 stainless steel sample substrate was activated with oxygen plasma for 1 min to eliminate the surface adsorbed water and generate more surface reactive groups.
[0075] Step 4: The activated biofilm 304 stainless steel sample is subjected to dry (chemical vapor deposition) silanization treatment. The biofilm 304 stainless steel sample is placed in a vacuum desiccator and treated with 100 μL of n-octyltriethoxysilane chemical vapor deposition at room temperature for 24 hours. The silane undergoes in situ hydrolysis and condensation reactions on the biofilm, thereby introducing a surface layer of repellent silane on the biofilm, that is, forming a silane hydrophobic layer on the surface of the biofilm structure of the 304 stainless steel sample, thereby obtaining a hydrophobic-biofilm structure coating of the 304 stainless steel sample.
[0076] Step 5: Take 20 μL of silicone oil and inject it into the hydrophobic-biofilm structure coating of the 304 stainless steel sample to form an outer coating through capillary absorption. Adjust the inclination angle of the 304 stainless steel sample so that the lubricant is evenly and fully covered on the surface of the hydrophobic-biofilm structure coating of the 304 stainless steel sample to obtain an ultra-slip coating with a biofilm structure.
[0077] Performance Analysis 1. Analysis of coating physical and chemical properties: 1.1 Coating thickness analysis: Four groups of identical 304 stainless steel samples were placed in the bacterial culture solution of the mesophilic Adhesive Bacillus in Example 1 and the bacterial culture solution of the Oneida Shewanella in Comparative Example 1, respectively, and cultured for 1 day, 4 days, 7 days, and 14 days, and then subjected to the same curing operation to obtain biofilm 304 stainless steel samples, and then the biofilm 304 stainless steel samples were stained with crystal violet. The biofilm forming ability of the bacteria Mesophilic Adhesive Bacillus and Oneida Shewanella was compared by the crystal violet staining results after different culture days; Figure 1 As shown, OD was measured by microplate reader 570nm From the absorbance values at 4 days of culture, it can be seen that the absorbance of the biofilm of the mesophilic adhesin Bacillus is twice that of the biofilm structure of Shewanella Oneida after 4 days of culture. After 14 days of culture, the absorbance of the mesophilic adhesin Bacillus is 7 times that of Shewanella Oneida, indicating that the bacteria selected in the present invention have stronger film-forming ability and are more conducive to the construction of structural scaffolds.
[0078] 1.2 Analysis of coating surface morphology: The surface structure and roughness of the biofilm scaffold structure, the hydrophobic-biofilm structure coating, and the highly adhesive biofilm structure super-slip antifouling coating of the 304 stainless steel sample in Example 1 were observed using an atomic force microscope (AFM). Figure 2As shown, the deposited silane monolayer produces a highly integrated biofilm skeleton with enhanced root mean square roughness (RMS). The roughness of the ultra-slip antifouling coating with a high adhesion biofilm structure is 15.05 nm, which is lower than the roughness of the biofilm structure (38.2 nm) and the hydrophobic-biofilm structure coating (46.92 nm). This is because the lubricant fills the unevenness on the surface of the hydrophobic-biofilm structure coating, giving it ultra-slip properties.
[0079] 1.3 Analysis of coating chemical structure: like Figure 3 As shown, Fourier transform infrared spectroscopy (FTIR) was used to show the evolution of the covalent grafting of the hydrophobic-biofilm structure coating in Example 1, and it was found that the Si-O antisymmetric stretching vibration was at 1017 cm -1 A new characteristic peak appeared at 3100cm -1 - 3700cm -1 The broad characteristic peaks between them are attributed to the overlap of the OH stretching vibration of the polysaccharide and the NH stretching vibration of the protein. The results indicate that more chemical reaction sites are generated on the surface of the hydrophobic-biofilm structure coating, which is beneficial to the subsequent surface modification.
[0080] 1.4 Coating element distribution analysis: like Figure 4 As shown in Figure 2, the structural observations of transmission electron microscopy (TEM) and high-angle annular dark field scanning TEM images show that after silane functionalization, the surface of the bioscaffold structure retains the typical rod-like morphology, such as Figure 5 As shown, the corresponding energy dispersive spectroscopy (EDS) diagram shows that C, N, and O are evenly distributed, and the enhanced distribution of Si element is consistent with the bacterial outline, verifying the successful binding of Si element on the coating surface.
[0081] 1.5 Analysis of coating light transmittance: Due to the universality of the adhesion of mesophilic adhesin bacteria, the ultra-slip antifouling coating with a high-adhesion biofilm structure in Example 6 of the present invention is also suitable for being made on a transparent substrate glass, such as Figure 6 As shown, the optical properties of blank glass, hydrophobic-biofilm structure coating and super-slip antifouling coating with high adhesion biofilm structure on transparent substrate glass were compared by comparing the transmittance in the visible light range of 400nm-800nm. Compared with the blank glass with a transmittance of 90.0%, the transmittance of the hydrophobic-biofilm structure coating on the transparent substrate glass was slightly reduced to 79.1%. However, due to the smooth morphology of the super-slip antifouling coating with high adhesion biofilm structure, its transmittance was close to that of the blank glass at 89.4%. Therefore, the influence of the super-slip antifouling coating with high adhesion biofilm structure of the present invention on transparency can be ignored.
[0082] 2. Analysis of coating hydrophobicity: 2.1 Wettability analysis: The sliding effect of water droplets on the coating surface was measured by measuring the water contact angle and sliding angle on the surface of the super-slip antifouling coating with high adhesion biofilm structure, as well as the sliding angle on samples of different shapes; The contact angle of pure water (the contact angle of a 4 μL water droplet) and the sliding angle (the tilt angle required for a 6 μL water droplet to move) were measured using a contact angle meter to evaluate the surface wettability of the coating at different biofilm culture days; According to the preparation method of the ultra-slip antifouling coating with high adhesion biofilm structure in Example 1, only the culture time of the 304 stainless steel sample in the bacterial culture solution was changed. After culturing for 1 day, 4 days, 7 days and 14 days in groups, the droplet migration rate of the ultra-slip antifouling coating with high adhesion biofilm structure prepared was observed. The ultra-slip antifouling coating with high adhesion biofilm structure in each group was composed of biofilm nanotexture, such as Figure 7 As shown in the figure, the biofilm with a short culture time (1 day) has a thin and incomplete framework, which leads to an unstable lubricating layer. Although the lubricant can maintain a stable wet morphology, the liquid repellency is poor. When the culture time of the biofilm nanostructure on the 304 stainless steel sample is extended, the thicker biofilm (such as 7 days or 14 days) shows a higher surface roughness, and the droplets enter the Wenzel state with a pinning effect. The water contact angle of the super-slip antifouling coating of the highly adhesive biofilm structure cultured for 4 days is 104.3 ° , water sliding angle is 1.8 ° , as the critical point of surface level change provides excellent sliding properties, therefore, culturing for 4 days is the preferred solution for the biofilm structure of the preferred 304 stainless steel substrate.
[0083] 2.2 Universal analysis of material substrate: Examples 5 to 11 are respectively ultra-slip antifouling coatings with high adhesion biofilm structures prepared on different substrates, with 25 ° The contact angle of pure water (the contact angle of a 4μL water droplet) and the sliding angle (the tilt angle required for the movement of a 6μL water droplet) were measured by a contact angle meter to explore the sliding effect of the ultra-slip antifouling coating with a high adhesion biofilm structure prepared by droplets on different substrates, such as Figure 8 As shown in Figure 2, after the super-slip antifouling coating with high adhesion biofilm structure was prepared on Ti, Al, 304 stainless steel, 2205 stainless steel, Teflon and PET samples, the water sliding angle was less than 5 °This is due to the biofilm scaffold structure with strong interface anchoring ability and high cohesion, so the ultra-slip antifouling coating with high adhesion biofilm structure can be uniformly attached to various metal, inorganic and organic substrates and give them hydrophobic (liquid-repellent) properties, which strongly proves that the ultra-slip antifouling coating with high adhesion biofilm structure of the present invention has universal applicability to various material types.
[0084] The ultra-slip antifouling coating 304 stainless steel sample and Teflon sample of the high adhesion biofilm structure in Example 5 and Example 7 were prepared at 25 ° Tilt angle, such as Fig. 9 , Fig.10 As shown, it was observed that the dye-labeled water droplets slid effortlessly along the inclined substrate of the ultra-slip antifouling coating with a high-adhesion biofilm structure without leaving any residue. In contrast, the bare substrate, even on the low surface energy material Teflon, was completely soaked and contaminated by water, indicating that the ultra-slip antifouling coating with a high-adhesion biofilm structure of the present invention has excellent hydrophobic properties.
[0085] The method for preparing the biofilm of the present invention is easy to implement and is suitable for producing a uniform antifouling coating on the inner surface. In Example 12, an ultra-slip antifouling coating with a high adhesion biofilm structure is prepared on the inner wall of a PVC pipe with an inner diameter of 3 mm. Fig.11 As shown, 10 μL of dyed water was placed at the open end of the PVC tube with the super-slippery antifouling coating of the high-adhesion biofilm structure. The water droplets could easily pass through the inner wall of the tube without being stained. In contrast, the blank group PVC tube showed that the liquid easily adhered to its inner wall, which also indicates that the super-slippery antifouling coating of the high-adhesion biofilm structure of the present invention also has shape universality.
[0086] 2.3 Analysis of coating bending resistance: Example 8 An ultra-slip antifouling coating with a high adhesion biofilm structure was prepared on a PET substrate of 7.62 cm×2.54 cm in size and bent into U, V and S shapes. The sliding angle was measured after repeated bending and releasing for 1000 times; like Fig.12 As shown, the bending test results of the super-slip antifouling coating with a high adhesion biofilm structure prepared on a flexible PET sheet are shown, wherein the super-slip antifouling coating with a high adhesion biofilm structure on the PET sheet can be folded into different shapes in sequence, and no delamination or damage was observed on the coating during the bending process and after recovery. Even more than 1,000 twistings and multiple foldings failed to prevent the sliding behavior of the super-slip antifouling coating with a high adhesion biofilm structure, which indicates that our coating has excellent bending resistance.
[0087] 3. Analysis of coating anti-corrosion performance: Electrochemical tests were performed using a three-electrode device containing 250 mL of solution at 30 °C. The corrosive Pseudomonas aeruginosa was selected as the experimental strain, and a saturated calomel electrode, a platinum sheet electrode, and a coated electrode were selected as the reference electrode, the counter electrode, and the working electrode, respectively. The electrochemical impedance spectroscopy (EIS) data were obtained at 10 5 Hz to 10 -2 Hz frequency range, with an amplitude of 5mV; 3.1 Effective physical barriers: Mesophilic Adhesive Bacillus plays a vital role in corrosion protection due to its strong biofilm-forming ability; cohesive EPS is the main component of the biofilm, which can firmly adhere to the native metal surface or oxide layer through strong and stable secondary chemical bonds, electrostatic interactions, hydrogen bonds and van der Waals interactions, including hydrophobic forces; as determined by the compositional analysis of extracellular polymers, this sustainably produced dense biopolymer matrix provides a physical barrier at the metal-coating interface in a highly cohesive biofilm, effectively shielding corrosive substances such as oxygen and chloride ions; 3.2 Electrochemical test: The blank group 304 stainless steel substrate, the ultra-lubricated 304 stainless steel substrate with the biofilm structure of Shewanella Oneida in Comparative Example 1, and the ultra-lubricated antifouling coated 304 stainless steel substrate with the high-adhesion biofilm structure in Example 1 were immersed in simulated seawater containing corrosive Pseudomonas aeruginosa for 4 days, and the anti-corrosion performance was tested by electrochemical measurement. The results were analyzed by electrochemical impedance spectroscopy (EIS) to study the effect of the high-adhesion biofilm structure design of the mesophilic adhesin Bacillus on the corrosion protection of the substrate.
[0088] like Fig.13 As shown, according to the electrochemical impedance spectrum, compared with the ultra-lubricated 304 stainless steel substrate with the biofilm structure of Shewanella Onida in Comparative Example 1, the ultra-lubricated antifouling coating 304 stainless steel substrate with the high-adhesion biofilm structure of Bacillus mesophilus in Example 1 has a much larger capacitance loop diameter than the blank group 304 stainless steel substrate, which indicates that the formation of a compact biofilm structure of Bacillus mesophilus increases the charge transfer resistance, and the dead biofilm formed by pre-fixation with glutaraldehyde does not provide continuous metabolic activity and also exhibits significant corrosion inhibition, confirming that this anti-corrosion ability is mainly attributed to extracellular polymers (EPS) rather than cell viability.
[0089] 4. Analysis of coating antifouling performance: The various stages of biofouling: protein adhesion (modulation biofilm stage); bacterial adhesion (unstable biofilm stage); algae adhesion (colonization biofilm stage).
[0090] Stages of formation of biofouling layer on solid surface of the seabed: First, any object invading seawater will adsorb a layer of organic matter, mainly proteins and polysaccharides, on the surface within a few minutes, then bacteria and algae will successively attach to the finishing film, secrete extracellular metabolites, form biofilm, fungi and larvae of large fouling organisms grow and develop in the film, and finally form a complex large fouling biological layer; the ultra-slip antifouling coating with high adhesion biofilm structure acts as a slippery surface to prevent the stable attachment of fouling organisms, and provides a more controllable and stable surface by regulating interfacial tension and solubility of liquid in water. In this study, bovine serum albumin (BSA), Gram-positive Staphylococcus aureus, Vietnamese Bacillus and Gram-negative Escherichia coli, which are common in marine environment and daily life environment, and Chlorella and Isochrysis, which are widely distributed in the ocean, were used for exploration.
[0091] 4.1 Protein resistance: The anti-protein performance was quantified using an adsorption test, in which a higher concentration of BSA with 2 mg / mL-4 mg / mL was applied for immersion culture for 24 h, the firmly bound proteins on the sample were extracted by vigorous washing with sterile water, and the relative amount of BSA adhered to the surface was quantified by measuring the absorbance of the collected washing solution at λ = 280 nm; The 304 stainless steel samples of the hydrophobic-biofilm structure coating, the ultra-slip antifouling coating with high adhesion biofilm structure, and the blank group 304 stainless steel samples in Example 1 were immersed in BSA solution for 24 hours, and the adsorption amount on the sample surface was quantitatively analyzed. The residual BSA on the hydrophobic-biofilm structure coating and the ultra-slip antifouling coating with high adhesion biofilm structure was only 0.45±0.002 mg·cm -2 , 0.23±0.05mg·cm -2 , while the residual BSA on the bare 304 stainless steel sample was as high as 0.83±0.05 mg·cm -2 , indicating that the lubricating layer reduces the contact and adsorption of proteins on the surface, proving that the ultra-slip antifouling coating with a high-adhesion biofilm structure has excellent protein resistance. The ultra-slip antifouling coating with a high-adhesion biofilm structure of the present invention has a protein resistance of 72.3%. The protein resistance calculation formula is as follows: Protein resistance = (BSA 空白组 -BSA 实验组 ) / BSA 空白组 ×100% 4.2 Bacterial resistance: In the process of marine pollution, bacteria play a vital role in the construction of biofilms. Escherichia coli (Gram-negative bacteria), Staphylococcus aureus and Bacillus vietnam (Gram-positive bacteria) were used as model bacteria to investigate the antibacterial properties of the ultra-slip antifouling coating with a high adhesion biofilm structure of the present invention. All materials for antibacterial evaluation were sterilized by ultraviolet irradiation for 30 minutes before use. The single bacteria Escherichia coli, Staphylococcus aureus and Bacillus vietnam isolated by the plate streak method were inoculated in 2216E or Luria-Bertani liquid culture medium, respectively, and cultured at 37°C for 12h-16h to the logarithmic growth phase. The bacterial solution in the logarithmic growth phase was diluted to obtain a bacterial solution of appropriate concentration for subsequent experiments.
[0092] 2 ml of Escherichia coli bacterial suspension was added to a 24-well culture plate, and the hydrophobic-biofilm structure coating, the ultra-slip antifouling coating 304 stainless steel sample with high adhesion biofilm structure and the blank group 304 stainless steel sample in Example 1 were cultured at 37°C for 1 day, and then gently rinsed with a sterile PBS solution to remove the loosely adhered bacteria on the surface. The antibacterial ability of the samples was quantitatively studied by the dilution coating plate method, and the biofilm bacteria on the surface were collected, continuously diluted in a sterile PBS solution (pH=7.3), and then plated on an agar plate. After culturing at 37°C for 10 hours, the number of colonies on the plate was photographed and counted; A certain amount of Staphylococcus aureus bacterial suspension was added to a 24-well culture plate, and the hydrophobic-biofilm structure coating, the ultra-slip antifouling coating 304 stainless steel sample with a high-adhesion biofilm structure, and the blank group 304 stainless steel sample were cultured at 37°C for 1 day, and then gently rinsed with a sterile PBS solution to remove the loosely adhered bacteria on the surface. The antibacterial ability of the samples was quantitatively studied by the dilution coating plate method, and the biofilm bacteria on the surface were collected, continuously diluted in a sterile PBS solution (pH=7.3), and then plated on an agar plate. After culturing at 37°C for 14 hours, the number of colonies on the plate was photographed and counted; A certain amount of Vietnamese Bacillus bacterial suspension was added to a 24-well culture plate, and the hydrophobic-biofilm structure coating, the ultra-slip antifouling coating 304 stainless steel sample with a high-adhesion biofilm structure, and the blank group 304 stainless steel sample were cultured at 37°C for 1 day, and then gently rinsed with a sterile PBS solution to remove the loosely adhered bacteria on the surface. The antibacterial ability of the samples was quantitatively studied by the dilution coating plate method, and the biofilm bacteria on the surface were collected, continuously diluted in a sterile PBS solution (pH=7.3), and then plated on an agar plate. After culturing at 37°C for 10 hours, the number of colonies on the plate was photographed and counted; The antimicrobial properties of different coatings were evaluated by quantifying viable bacteria using the dilution spread plate method, e.g. Fig.14As shown, in the hydrophobic-biofilm structure coating sample, compared with the blank group, the percentage of active cells in the biofilm of Escherichia coli, Staphylococcus aureus and Vietnamese Bacillus was not significantly reduced, but the super-slip anti-fouling coating with high adhesion biofilm structure was compared with the blank group, and the colony forming unit (CFU) counts of Escherichia coli, Staphylococcus aureus and Vietnamese Bacillus biofilm were reduced by 2.0log, 1.1log and 2.0log, respectively. The super-slip anti-fouling coating with high adhesion biofilm structure of the present invention has a bacterial resistance of 96.28%, and the bacterial resistance calculation formula is as follows: Bacterial resistance = (CFU 空白组 -CFU 实验组 ) / CFU 空白组 ×100% 4.3 Algae resistance: Algae are also one of the main causes of the second stage of marine biofouling. The anti-algae performance of the ultra-slip antifouling coating with high adhesion biofilm structure was tested using Chlorella and Isochrysis algae. Before the experiment, ultraviolet sterilization was used for 30 minutes to purify all the culture media, pipettes and other experimental supplies required for co-cultivation. Two different algae strains, Chlorella and Isochrysis, were used as experimental microalgae species. The two microalgae were cultured in F / 2 culture medium, respectively, under visible light (LED) illumination (3000 lux) and 20°C for 8 days. The algae solution in the logarithmic growth phase was diluted with culture medium to obtain an appropriate concentration (10 5 Cells·mL -1 ), the hydrophobic-biofilm structure coating, the ultra-slip antifouling coating 304 stainless steel sample with high adhesion biofilm structure in Example 1 and the blank group 304 stainless steel sample were immersed in these diluted algae suspensions for 7 days under a light cycle of daylight and darkness, and then thoroughly rinsed with a sterile PBS solution (pH=7.3) to remove loosely attached algae, and the anti-algae ability of the ultra-slip antifouling coating with high adhesion biofilm structure was studied by measuring the absorbance at λ=440nm, and the absorbance represents the algae biomass; like Fig.15 As shown, it can be seen that during the growth process, according to the characteristic absorption signal, the algae sedimentation difference between the test surfaces is significant, the algae coverage rate of the ultra-slip antifouling coating with a high adhesion biofilm structure is low, and the anti-algae mechanism of the ultra-slip antifouling coating with a high adhesion biofilm structure is similar to the antibacterial mechanism, which is related to the physical barrier of the lubricant. The ultra-slip antifouling coating with a high adhesion biofilm structure of the present invention has an algae resistance of 85.72%, and the algae resistance calculation formula is as follows: Algae resistance = (absorbance 空白组 -Absorbance 实验组 ) / absorbance 实验组 ×100%.
Claims
1. A method for preparing an ultra-slip antifouling coating with a high-adhesion biofilm structure, characterized in that: The steps include: Step 1: Cultivate the mesophilic adhesin bacteria, adjust the bacterial concentration, obtain a bacterial culture solution, place the material sample in the bacterial culture solution for cultivation, and cover the surface of the material sample with a biofilm scaffold structure; Step 2: The material sample covering the biofilm scaffold structure is appropriately rinsed aseptically to remove floating bacteria, and fixed with glutaraldehyde to obtain a biofilm material sample base; Step 3: Activate the biofilm material sample substrate to eliminate surface adsorbed water and generate more surface reactive groups; Step 4: performing dry or wet silanization treatment on the activated biofilm material sample substrate to deposit hydrophobic silane on the biofilm structure surface of the material sample to obtain a hydrophobic-biofilm structure coating of the material sample; Step 5: Inject the lubricant into the hydrophobic-biofilm structure coating of the material sample, absorb it through capillary force to form an outer coating, adjust the inclination angle of the material sample so that the lubricant is evenly and fully covered on the surface of the hydrophobic-biofilm structure coating of the material sample, and obtain an ultra-slip anti-fouling coating with a high adhesion biofilm structure.
2. The method for preparing a super-slip antifouling coating with a high-adhesion biofilm structure according to claim 1, characterized in that: In step 1, the mesophilic adhesin Bacillus is cultured by inoculating the separated single colony of the mesophilic adhesin Bacillus into 2216E liquid culture medium using a plate streak method, the culture temperature is 20° C.-40° C., and the culture is carried out until it is in the logarithmic growth phase.
3. The method for preparing a super-slip antifouling coating with a high-adhesion biofilm structure according to claim 1, characterized in that: Adjust the bacterial concentration in step 1 to 10 5 CFU / mL-10 8 CFU / mL.
4. The method for preparing a super-slip antifouling coating with a high-adhesion biofilm structure according to claim 1, characterized in that: The material samples described in step 1 include metal, glass and polymer. The metal samples are surface polished, cleaned and dried before being placed in the bacterial culture solution. The glass and polymer samples are cleaned and dried before being placed in the bacterial culture solution. The material samples are cultured in the bacterial culture solution for 3 to 5 days.
5. The method for preparing a super-slip antifouling coating with a high-adhesion biofilm structure according to claim 1, characterized in that: In step 2, sterile phosphate buffer is used for sterile flushing; The concentration of glutaraldehyde in glutaraldehyde fixation is 2%-6% v / v, and the fixation time is 2h-8h.
6. The method for preparing a super-slip antifouling coating with a high-adhesion biofilm structure according to claim 1, characterized in that: In step 3, activation is performed by oxygen plasma treatment for 1 min to 5 min.
7. The method for preparing a super-slip antifouling coating with a high-adhesion biofilm structure according to claim 1, characterized in that: In step 4, the dry silanization treatment is to place the biofilm material sample in a vacuum desiccator and treat it with n-octyltriethoxysilane chemical vapor deposition at room temperature; The wet silanization treatment is to immerse the biofilm material sample in an ethanol / water solution containing n-octyltriethoxysilane.
8. The method for preparing a super-slip antifouling coating with a high-adhesion biofilm structure according to claim 7, characterized in that: In step 4, in the dry silanization treatment, octyltriethoxysilane is used for chemical vapor deposition treatment for 12h-36h; The volume ratio of n-octyltriethoxysilane to ethanol / water solution in wet silanization treatment is 1:1, and the immersion time is 3h-6h.
9. The method for preparing a super-slip antifouling coating with a high-adhesion biofilm structure according to claim 1, characterized in that: In step 5, the lubricant is silicone oil.
10. An ultra-slip antifouling coating with a high-adhesion biofilm structure, characterized in that: The method for preparing an ultra-slip antifouling coating with a high-adhesion biofilm structure as described in any one of claims 1 to 9 is used for preparation. The ultra-slip antifouling coating is a porous surface of an anti-corrosion biofilm structure injected with a smooth liquid, uses the biofilm as a support structure, has a nano-scale texture, deposits hydrophobic silane on the surface of the biofilm structure, and is compounded with a lubricant.
Citation Information
Patent Citations
Electrodeposition method of super-hydrophobic and super-smooth coating on surface of weathering resistant steel
CN116288576A
Metal matrix surface composite coating as well as preparation method and application thereof
CN117926362A
Green self-repairing super-smooth surface marine antifouling coating and preparation method thereof
CN114806397A
Functionalization of mycelium material
CN116745401A
Super-smooth anti-fouling coating with synergistic function of dispersing and killing fouling organisms and preparation of super-smooth anti-fouling coating
CN118852934A